PROMOTING MEANINGFUL LEARNING THROUGH CREATE-SHARE-COLLABORATE - Siti Nazuar Sailin; Noor Aida Mahmor (Proceedings of The ICECRS, 2016)
Students in this 21st century are required to acquire these 4C skills: Critical thinking, Communication, Collaboration and Creativity. These skills can be integrated in the teaching and learning through innovative teaching that promotes active and meaningful learning. One way of integrating these skills is through collaborative knowledge creation and sharing. This paper providesan example of meaningful teaching and learning activities designed within the Create-Share-Collaborate instructional strategy by utilizing Web 2.0 tool namely Popplet.